Microstructure of interpass rolled wire + arc additive manufacturing Ti-6Al-4V components - Martina, Filomeno; Colegrove, Paul A.; Williams, Stewart W. (Springer, 2015)
Mechanical property anisotropy is one of the issues that are limiting the industrial adoption of additive manufacturing (AM) Ti-6Al-4V components. To improve the deposits’ microstructure, the effect of high-pressure interpass rolling was evaluated, and a flat and a profiled roller were compared. The microstructure was changed from large columnar prior beta grains that traversed the component to equiaxed grains that were between 56 and 139 μm in size. The repetitive variation in Widmanstätten alpha lamellae size was retained; however, with rolling, the overall size was reduced. A “fundamental study” was used to gain insight into the microstructural changes that occurred due to the combination of deformation and deposition. High-pressure interpass rolling can overcome many of the shortcomings of AM, potentially aiding industrial implementation of the process.
Keywords: Metallic materials; Characterization and evaluation of materials; Structural materials; Surfaces and interfaces, thin films; nanotechnology